Scytolyngbya timoleontis, gen. et sp. nov. (Leptolyngbyaceae, Cyanobacteria): a novel false branching Cyanobacteria from China - Song, Gaofei; Jiang, Yongguang; Li, Renhui (Phytotaxa, 2015)
A novel genus within Leptolyngbyaceae related to Leptolyngbya morphotypes, Scytolyngbya, gen. nov., is described based on a polyphasic approach in the present study. From a freshwater sample with filaments of oscillatorean cyanobacteria from a well in Hubei Province, China, Scytolyngbya (type species: Scytolyngbya timoleontis, sp. nov.) was found to possess richly and repeatedly false branches and thick sheaths, which distinguishs this genus from Leptolyngbya sensu stricto. Phylogenetic analysis based on 16S rRNA sequences showed that this species was clustered into the Leptolyngbyaceae and separated from the type species Leptolyngbya boryana. The secondary structures of 16S-23S rRNA intergenic spacer of Scytolyngbya timoleontis did not correspond to any previously described species in cyanobacteria.